2015
DOI: 10.1016/j.plantsci.2015.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Cell wall modifications triggered by the down-regulation of Coumarate 3-hydroxylase-1 in maize

Abstract: Coumarate 3-hydroxylase (C3H) catalyzes a key step of the synthesis of the two main lignin subunits, guaiacyl (G) and syringyl (S) in dicotyledonous species. As no functional data are available in regards to this enzyme in monocotyledonous species, we generated C3H1 knockdown maize plants. The results obtained indicate that C3H1 participates in lignin biosynthesis as its down-regulation redirects the phenylpropanoid flux: as a result, increased amounts of phydroxyphenyl (H) units, lignin-associated ferulates a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 65 publications
0
34
0
Order By: Relevance
“…Such a redirection of the flux would have a particularly strong effect in the C2 background that has a high flux toward flavonoids. Recently, it was reported that stems of C3H1-RNAi (for RNA interference) maize plants (which produce less lignin) have increased levels of tricin, consistent with a redirection of the carbon flux to the synthesis of flavonoids instead of the canonical monolignols (Fornalé et al, 2015). In the leaves of maize C2-Idf mutants, the reverse takes place: a substantial redirection of the carbon flux from the biosynthesis of flavonoids to the biosynthesis of the canonical monolignols.…”
Section: Discussionmentioning
confidence: 94%
“…Such a redirection of the flux would have a particularly strong effect in the C2 background that has a high flux toward flavonoids. Recently, it was reported that stems of C3H1-RNAi (for RNA interference) maize plants (which produce less lignin) have increased levels of tricin, consistent with a redirection of the carbon flux to the synthesis of flavonoids instead of the canonical monolignols (Fornalé et al, 2015). In the leaves of maize C2-Idf mutants, the reverse takes place: a substantial redirection of the carbon flux from the biosynthesis of flavonoids to the biosynthesis of the canonical monolignols.…”
Section: Discussionmentioning
confidence: 94%
“…5E). It has been reported that disruptions in the monolignol biosynthetic pathway redirect the metabolic flux in the phenylpropanoid pathway and occasionally affect accumulations of flavonoids (Abdulrazzak et al, 2006;Besseau et al, 2007;Fornalé et al, 2010;Li et al, 2010;Vanholme et al, 2012;Fornalé et al, 2015). Therefore, it is conceivable that a blockage in a flavonoid pathway may, in turn, affect the generation of monolignols and their lignin polymers.…”
Section: Fnsii Mutant Rice Produces Cell Wall Lignins Devoid Of Tricinmentioning
confidence: 99%
“…Subsequently, extensive surveys have revealed that tricin-bound lignins exist abundantly, particularly in the monocot family Poaceae, which comprises grasses including cereals. They also have been found in some commelinid monocot families outside Poaceae, such as Arecaceae (palms) and Bromeliaceae (pineapples and relatives), the noncommelinid family Orchidaceae (the orchids), particularly in the genus Vanilla, and also in certain dicots (Rencoret et al, 2013;Wen et al, 2013;Del Río et al, 2015;Lan et al, 2015Lan et al, , 2016aLan et al, , 2016bKoshiba et al, 2017).…”
mentioning
confidence: 96%
“…Moreover, the two CYP450 genes were also involved in the “Flavonoid biosynthesis” pathway (Supplementary Table S8). In these pathways, the two CYP450 genes encoded the C3H which catalyze the p -coumaric acid, p -coumaroyl-CoA and p -coumaraldehyde to caffeic acid, caffeoyl-CoA and caffeyl aldehyde, respectively ( Figure 6 and Supplementary Figure S2) (Xue et al, 2014; Fornaléa et al, 2015), so, we named these two genes as SlC3H1 ( Solyc10g078220 ) and SlC3H2 ( Solyc10g078230 ). In addition, the six POD genes were involved in the last step of biosynthesis of lignin, an insoluble cell wall-associated polymer ( Figure 6 ) (Quiroga et al, 2000; Higuchi, 2006).…”
Section: Resultsmentioning
confidence: 99%